Early transmissible ampicillin resistance in zoonotic Salmonella enterica serotype Typhimurium in the late 1950s: a retrospective, whole-genome sequencing study. Issue 2 (February 2018) - Tran-Dien, Alicia; Le Hello, Simon; Bouchier, Christiane; Weill, François-Xavier
Summary: Background: Ampicillin, the first semi-synthetic penicillin active against Enterobacteriaceae, was released onto the market in 1961. The first outbreaks of disease caused by ampicillin-resistant strains of Salmonella enterica serotype Typhimurium were identified in the UK in 1962 and 1964. We aimed to date the emergence of this resistance in historical isolates of S enterica serotype Typhimurium. Methods: In this retrospective, whole-genome sequencing study, we analysed 288 S enterica serotype Typhimurium isolates collected between 1911 and 1969 from 31 countries on four continents and from various sources including human beings, animals, feed, and food. All isolates were tested for antimicrobial drug susceptibility with the disc diffusion method, and isolates shown to be resistant to ampicillin underwent resistance-transfer experiments. To provide insights into population structure and mechanisms of ampicillin resistance, we did whole-genome sequencing on a subset of 225 isolates, selected to maximise source, spatiotemporal, and genetic diversity. Findings: 11 (4%) of 288 isolates were resistant to ampicillin because of acquisition of various β lactamase genes, including bla TEM-1, carried by various plasmids, including the virulence plasmid of S enterica serotype Typhimurium. These 11 isolates were from three phylogenomic groups. One isolate producing TEM-1 β lactamase was isolated in France in 1959 and two isolates producing TEM-1 β lactamase were isolated in Tunisia in 1960, before ampicillin went on sale. The vectors for ampicillin resistance were different from those reported in the strains responsible for the outbreaks in the UK in the 1960s. Interpretation: The association between antibiotic use and selection of resistance determinants is not as direct as often presumed. Our results suggest that the non-clinical use of narrow-spectrum penicillins (eg, benzylpenicillin) might have favoured the diffusion of plasmids carrying the bla TEM-1 gene in S enterica serotype Typhimurium in the late 1950s. Funding: Institut Pasteur, Santé publique France, the French Government's Investissement d'Avenir programme, the Fondation Le Roch-Les Mousquetaires.